Cosmografías musicales en culturas prehispánicas del suroccidente Colombiano - Pinilla Higuera, Germán (Libros de Investigación., 2009)
Musicological research in the archaeological context are very rare and have not been sufficiently disseminated in academic circles. This study inventories and describes items collected, studied and categorized in different museums in Colombia and those are significant collections of various musical instruments in various archaeological materials and technologies. There is an emphasis on the iconographic/artistic elements of the instruments.